Effect of the parthenocarpy gene P1 and ploidy in bunch and fruit traits of plantain and banana hybrids - Ortíz, R.; Vuylsteke, D.R. (1995)
Plantain and banana (Musa spp. AAB and AAA groups) are perennial giant herbs of the tropics which develop parthenocarpic fruits. At least three independent but complementary dominant genes control vegetative parthenocarpy in Musa. One of these genes, P1 segregates in euploid hybrid progenies derived from crosses between triploid 'French' plantains and a wild nonedible diploid banana. Linear correlation and regression analyses revealed that bunch weight and fruit weight and size were positively influenced by both ploidy increases and change of recessive to dominant alleles at the P1 locus. Moreover, significant multiple regression models, including ploidy and number of copies of the P1 allele as independent variables, accounted for most of the phenotypic variation for bunch and fruit traits. The coefficients of determination of the multiple regression analyses were always smaller than estimates of broad-sense heritability for each trait. This implies that ploidy and the effect of allele substitution did not explain all the genetic variation for bunch and fruit traits. Hence, other genetic factors may explain the remaining portion of genetic variation. The potential for indirect marker-assisted selection in the seedling nursery, through the utilization of predictive multiple regression equations, was assessed by the Durbin-Watson test of residuals. The adoption of this breeding method requires the identification of DNA markers linked to the P1 gene and reliable and rapid methods to determine ploidy in seedlings